Sistem Pakar dengan Metode Forward Chaining untuk Diagnosis Penyakit dan Hama Tanaman Semangka - Pati, Muhammad Ibnu; Defit, Sarjon; Nurcahyo, Gunadi Widi (Rektorat Universitas Putra Indonesia YPTK Padang, 2020)
Watermelon crops are in demand by farmers to cultivate. Diseases and Pests are not separated from watermelon crops experienced by farmers. To overcome this, farmers rely solely on rough living and getting information from others, this is ineffective because watermelon plant experts are very limited. An expert system is the solution to the limitations of an expert in their field. In this expert system use advanced chain methods and website-based applications. This expert system can be accessed online for users who need information, consultation of diseases and pests on watermelon plants. The expert system will diagnose the symptoms that will be answered by the user of the application and will produce conclusions along with solutions from diseases and pests of watermelon plants. With expert limitations online system is no longer an obstacle for watermelon plant farmers. Information and consultation of diseases and pests of watermelon plants biased online without having to meet with experts.